2013
DOI: 10.1590/s1806-37132013000300011
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for infection with multidrug-resistant bacteria in non-ventilated patients with hospital-acquired pneumonia

Abstract: OBJECTIVE: To identify risk factors for the development of hospital-acquired pneumonia (HAP) caused by multidrug-resistant (MDR) bacteria in non-ventilated patients. METHODS: This was a retrospective observational cohort study conducted over a three-year period at a tertiary-care teaching hospital. We included only non-ventilated patients diagnosed with HAP and presenting with positive bacterial cultures. Categorical variables were compared with chi-square test. Logistic regression analysis was used to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 27 publications
1
36
1
2
Order By: Relevance
“…2), and found that HCAP is the most important predictor for MDROs (OR 14.2, 95% CI 1.734-115.9, p = 0.013) unlike previous studies [6][7][8][9]. Recently, the number of elderly patients with frequent hospital contacts has increased rapidly and many of these individuals are residing in nursing homes or long-term care facilities, especially in Korea [47], and those HCAP patients might be prone to MDR bacterial infection [48][49][50]. Such recent trends may explain why this study has shown results that are different from previous studies.…”
Section: Discussionmentioning
confidence: 89%
“…2), and found that HCAP is the most important predictor for MDROs (OR 14.2, 95% CI 1.734-115.9, p = 0.013) unlike previous studies [6][7][8][9]. Recently, the number of elderly patients with frequent hospital contacts has increased rapidly and many of these individuals are residing in nursing homes or long-term care facilities, especially in Korea [47], and those HCAP patients might be prone to MDR bacterial infection [48][49][50]. Such recent trends may explain why this study has shown results that are different from previous studies.…”
Section: Discussionmentioning
confidence: 89%
“…21 MDR infection in NVHAP is increasingly common in many parts of the world, resulting in the delayed administration of appropriate antibiotic therapy. [22][23][24] Moreover, attributable mortality from HAP may be greater than that associated with VAP because of the lower severity of illness existing at baseline in patients with HAP compared with those with VAP. 25 Several limitations of our study should be recognized.…”
Section: Discussionmentioning
confidence: 99%
“…In the same paper, pandrug-resistant (PDR) was defined as 'non-susceptibility to all agents in all antimicrobial categories' [5]. Common bacteria that show MDR/PDR are methicillin-resistant Staphylococcus aureus (MRSA), extended-spectrum beta-lactamase (ESBL)-producing bacteria, carbapenem-resistant Enterobacteriaceae (CRE), carbapenem-resistant Acinetobacter baumannii (A. baumannii, CRAB), MDR/PDR Pseudomonas aeruginosa (P. aeruginosa, MDR/PDRPA), and MDR Mycobacterium tuberculosis [6][7][8]. A high prevalence of nosocomial infections attributable to MDR strains has been reported in countries worldwide [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%